Molecular diagnosis and genotyping of Pneumocystis jirovecii in bronchoalveolar lavage samples obtained from patients with pulmonary disorder - Abdolmajid Fata (Current Medical Mycology, 2019)
Background and Purpose: Pneumocystis pneumonia (PCP) is one of the most common and life-threatening fungal diseases in patients with human immunodeficiency, treated with immunosuppressive medications. Immunocompetent people can also be a spreading agent for PCP. Regarding this, the aim of the present study was to diagnose and identify Pneumocystis jirovecii in bronchoalveolar lavage (BAL) samples obtained from patients with pulmonary disorder using a molecular method. Materials and Methods: For the purpose of the study, BAL samples (n=138) were collected from patients, undergoing bronchoscopy at the different departments of university hospitals affiliated to Mashhad University of Medical Sciences, Mashhad, Iran, during a period of one year (i.e., April 2014 until May 2015). Giemsa staining and molecular identification were carried out for each sample. The samples were also subjected to nested polymerase chain reaction (PCR), sequencing, and genotyping based on mitochondrial ribosomal large subunit (mtLSU rRNA) of P. jirovecii. The phylogenic tree was constructed by MEGA6 software. Results: The results of direct microscopic examination revealed the presence of P. jirovecii in 3 (2.2%) out of 138 samples; in addition, nested PCR and sequencing led to the detection of species in 17 (12.3%) samples. Out of patients with positive results, 10 (25%) and 7 (7.1%) cases were immunosuppressed and immunocompetent, respectively. The most common clinical symptoms among patients with pneumocystis were fever, dyspnea, and dry cough. In addition, genotypes III and II were the dominant genotypes in our dataset. Conclusion: Nested PCR and sequencing methods showed higher sensitivity and specificity as compared with a direct staining technique. Genotype III was identified as the most dominant type in patients with pulmonary disorder in Mashhad.